Literatura infantil e ditadura militar no Brasil (1964 – 1985): autores e livros que conseguiram driblar a censura - Lima, Brenda Kerlen Assunção (Brasil, 2025)
This research aimed to develop a greater understanding of children's literature during the military dictatorship, established in 1964, in Brazil and, at the same time, to perceive the mechanisms it found to criticize the government of the time, which was marked by actions of censorship, repression, violence and suppression of society's rights. To carry it out, we used the methodological tools of bibliographic and documentary research. From these, it was possible to identify how censorship impacted children's literature during the period of the military dictatorship; the mechanisms of criticism of the military dictatorship used by children's literature authors, especially Ruth Rocha; and, finally, how some literary works were configured as elements of resistance to the repression of this authoritarian government.